2019
DOI: 10.1186/s13722-019-0154-4
|View full text |Cite
|
Sign up to set email alerts
|

Rural access to MAT in Pennsylvania (RAMP): a hybrid implementation study protocol for medication assisted treatment adoption among rural primary care providers

Abstract: Background The continued escalation of opioid use disorder (OUD) calls for heightened vigilance to implement evidence-based care across the US. Rural care providers and patients have limited resources, and a number of barriers exist that can impede necessary OUD treatment services. This paper reports the design and protocol of an implementation study seeking to advance availability of medication assisted treatment (MAT) for OUD in rural Pennsylvania counties for patients insured by Medicaid in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Additionally, since this research was conducted in New York City participants likely had better access to MMT than in less urban geographic areas. Research has demonstrated the dearth of services for people who use illegal drugs in non-urban settings ( Jones, 2018 ; Cochran et al, 2019 ). Similarly, because of the clustering of harm reduction services in urban locations, participation in MMT is probably less stigmatizing than in other settings.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since this research was conducted in New York City participants likely had better access to MMT than in less urban geographic areas. Research has demonstrated the dearth of services for people who use illegal drugs in non-urban settings ( Jones, 2018 ; Cochran et al, 2019 ). Similarly, because of the clustering of harm reduction services in urban locations, participation in MMT is probably less stigmatizing than in other settings.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest challenges to date with increased buprenorphine prescribing for OUD remains financial concerns over insurance coverage, increased costs, and Medicaid reimbursement [29][30][31]. Evidence shows that increases in the price of buprenorphine/naloxone have the most pronounced negative effects on rural patients and patients from the south [29].…”
Section: Current State Changes and Challenges Of Buprenorphine Prescribing In Rural Areasmentioning
confidence: 99%
“…Along with this new legislation, improved insurance compensation must occur, and insurers should be encouraged to cover MOUD costs for longer periods and be discouraged from increasing out-of-pocket costs. Increased financial support from federal Medicaid and state-level Medicaid Managed Care Organizations (MCOs) should be pursued as it can improve access to MOUD for several rural patients and help them achieve and sustain sobriety [31]. In addition to this major financial barrier, other challenges shared by rural physicians are lack of a physician support network, lack of adequate clinic staff who were trained on caring for patients with OUD, a need to address mental health concerns through additional counseling, time restraints, legal regulations, stigma, and concerns over buprenorphine diversion [30,[32][33][34][35].…”
Section: Current State Changes and Challenges Of Buprenorphine Prescribing In Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be attributed to many reasons including lack of instruments and trained specialist surgeons. 8,9 There are many studies on the laparoscopic cholecystectomy in rural hospitals. It is important to understand whether the advantages of the laparoscopic cholecystectomy are there in the rural hospital set up.…”
Section: Introductionmentioning
confidence: 99%